Japanese guidance for use of biologics for psoriasis (the 2013 version). Issue 9 (5th September 2013) - Ohtsuki, Mamitaro; Terui, Tadashi; Ozawa, Akira; Morita, Akimichi; Sano, Shigetoshi; Takahashi, Hidetoshi; Komine, Mayumi; Etoh, Takafumi; Igarashi, Atsuyuki; Torii, Hideshi; Asahina, Akihiko; Nemoto, Osamu; et al.
Abstract: The clinical use of adalimumab and infliximab, human anti‐tumor necrosis factor (TNF)‐α monoclonal antibodies, for psoriasis began in January 2010. In January 2011, ustekinumab, a human anti‐interleukin‐12/23p40 (IL‐12/23p40) monoclonal antibody, was newly approved as the third biologic with an indication for psoriasis. While all of these biologics are expected to exhibit excellent therapeutic effect for psoriasis and to contribute to the improvement of quality of life in patients, these drugs require careful safety measures to prevent adverse drug reactions, such as serious infections. The new guidance, an English version prepared by revising the Japanese Guidance/Safety Manual for Use of Biologics for Psoriasis 2011 (in Japanese), is intended to provide up‐to‐date, evidence‐based recommendations and safety measures on the use of biologics, and describes the optimal use of the three biologics, medical requirements for facilities for using biologics, details of safety measures against reactivation of tuberculosis and hepatitis B virus infection, and recommendable combination therapies with biologics.